Intraoperative reversal of neuromuscular block with sugammadex or neostigmine during extreme lateral interbody fusion, a novel technique for spine surgery - Adamus, Milan; Hrabalek, Lumir; Wanek, Tomas; Gabrhelik, Tomas; Zapletalova, Jana (Journal of anesthesia, 2011)
PURPOSE: Extreme lateral interbody fusion (XLIF) is a method for stabilization of the lumbar spine. Intraoperatively, the surgeon identifies the lumbar nerve roots with a stimulator to prevent their injury. The objective of this study was to determine the extent to which shallow rocuronium-induced neuromuscular block must be intraoperatively reversed for reliable identification of nerve roots. METHODS: General anesthesia (midazolam-propofol-sufentanil-oxygen/air/sevoflurane-rocuronium) was administered to all patients. Train-of-four (TOF) stimulation of the ulnar nerve at 15-s intervals and electromyographic response of the adductor pollicis muscle were used. During operation, the surgeon stimulated the lumbar nerve roots (5-10 mA) to identify their course. At the appearance of two twitches to the TOF stimuli, sugammadex (2 mg/kg) or neostigmine (0.04 mg/kg) was administered. When the response to nerve root stimulation appeared, the TOF ratio was recorded. RESULTS: When the response to nerve root stimulation with 10 mA became detectable, the median (range) TOF ratios were 0.67 (0.50-0.81) and 0.65 (0.42-0.71) after sugammadex and neostigmine, respectively. Similarly, TOF ratios at the first detectable response to stimulation with 5 mA were 0.88 (0.67-0.93) and 0.83 (0.61-0.93). After sugammadex and neostigmine, the respective intervals until TOF ratio ≥0.90 were 2.0 (0.8-3.3) and 15.9 (7.3-28.8) min. CONCLUSION: Intraoperative reversal of shallow rocuronium-induced block with either sugammadex or neostigmine is an efficient method. For reliable detection of lumbar nerve roots with a stimulating current of 10 mA, the block should be reversed to a TOF ratio of at least 0.70. For a current intensity of 5 mA, the TOF ratio should reach 0.90.
Keywords: Lumbosacral Region; nedepolarizující myorelaxancia; rokuronium; Female; androstanoly; peroperační doba; Neostigmine; ženské pohlaví; Spinal Nerve Roots; neostigmin; gamma-Cyclodextrins; Androstanols; lidé; Anesthesia, General; Neuromuscular Nondepolarizing Agents; Spinal Fusion; Sugammadex; celková anestezie; Rocuronium; páteř; míšní kořeny; Spine; lumbosakrální krajina; nervosvalová blokáda; Male; Neuromuscular Blockade; fúze páteře; gama-cyklodextriny; lidé středního věku; mužské pohlaví; probouzení z anestezie; cholinesterasové inhibitory; Cholinesterase Inhibitors; Anesthesia Recovery Period; Middle Aged; Intraoperative Period; sugammadex; Humans